Integritas, Obedience Pressure, Kompleksitas Tugas dan Kualitas Audit Dengan Pengalaman Kerja Sebagai Variabel Moderasi - Pradhana, Made Aditya Bayu; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of integrity, obedience pressure and task complexity on audit quality with auditor's work experience as a moderating variable. The research was conducted at the Bali Provincial Inspectorate Office. The population in the study was all functional auditors at the Bali Provincial Inspectorate, amounting to 57 people. The sampling technique used is a saturated sample, which uses the entire population as the research sample. The data analysis technique used the Partial Least Square (PLS) 3.0 regression approach. The results showed that Integrity had a significant positive effect on audit quality. Obedience pressure has no significant negative effect on audit quality. Task complexity has a significant negative effect on audit quality. Auditor work experience does not moderate the effect of integrity, obedience pressure and task complexity on audit quality. Keywords: Integrity; Obedience Pressure; Task Complexity; Audit Quality; Work Experience.